Crustáceos no cerrito Ariano Souza, Rio Grande, Rio Grande do Sul e distribuição de Callinectes sapidus (Brachyura, Portunidae) - Santos,Cléverson Ranniéri M. dos (2004)
While all species of the genus Callinectes Stimpson, 1860 have a continuous distribution on the Atlantic coast of the Americas, Callinectes sapidus Rathbun, 1896 is the only one with disjunct distribution. Considering that this species was introduced in Europe and Japan, it has been suggested that the occurrence of C. sapidus on the southern coast of Brazil was due to the transport by ballast water. In the archaeological site Ariano Souza, located in the estuary of the Patos Lagoon (southern Brazil), remains of crustaceans, including claws of approximately two thousand years ago, were found. A preliminary analysis of this material showed Callinectes chelae. Because this archaeological site is located inside the estuary, it has been hypothesized that these chelae belong either to C. sapidus or to C. danae Smith, 1869. A comparison between pincers collected in the archaeological and pincers of these two species (90 dactyls, 30 of each type) was performed. The analysis (ANOVA) considered the variability of seven characters of the dactyls, and demonstrated the existence of two groups. Results showed that the measured characters suffice to separate these species, and indicated that the material found in the archaeological site belongs to C. sapidus. The hypothesis of the introduction of C. sapidus in the area is rejected. The possible biogeographic history of the species is discussed.